High-performance hydrogen sensor, preparation method and status monitoring system for early detection of thermal runaway of lithium-ion batteries

By designing a high-performance hydrogen sensor and using a sandwich structure with a catalytic sensitization layer, a gas-sensitive layer and an electron supply layer, the problem of early detection of thermal runaway in lithium-ion batteries is solved, and the rapid, sensitive and reliable detection of hydrogen is achieved, providing an effective early warning mechanism.

CN118275505BActive Publication Date: 2025-03-18CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410371948.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-03-18
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to thermal runaway under extreme conditions such as overcharging and fast charging, resulting in short circuits inside the battery and the generation of a large number of combustible gases. The prior art is difficult to effectively warn and detect.

Method used

A high-performance hydrogen sensor is designed, and a sandwich structure of catalytic sensitization layer, gas-sensitive layer and electron supply layer is adopted, including Ag@SnO2 catalytic sensitization layer, SnO2 gas-sensitive layer and g-C3N4 electron supply layer. The rapid detection and early warning of hydrogen is achieved through the preparation method and the state monitoring system.

Benefits of technology

It has achieved high sensitivity to hydrogen, short response/recovery time, good selectivity and repeatability, and can provide early warning in the early stage of thermal runaway of lithium-ion batteries, significantly reducing the occurrence of fire accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118275505B_ABST
    Figure CN118275505B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas sensors, and specifically relates to a high-performance hydrogen sensor for early detection of thermal runaway of lithium-ion batteries, a preparation method and a state monitoring system. The sensor comprises a sensing layer and a substrate, and the sensing layer is a sandwich structure consisting of a catalytic sensitization layer, a gas sensitive layer and an electron supply layer, which are Ag@SnO2 catalytic sensitization layer, SnO2 gas sensitive layer and g-C3N4 electron supply layer from top to bottom. The catalytic effect and overflow effect of Ag nanoparticles enable the sensor to have a shorter response / recovery time, a low detection limit, good stability and repeatability. At the same time, since the electron supply layer transports a large number of active electrons to the gas sensitive layer, coupled with the electron sensitization effect of the catalytic sensitization layer, the reaction activity of the gas sensitive layer is greatly improved, and the gas-sensitive performance of the sensor is further improved. The sensor has a high response value and good selectivity, and can well warn the occurrence of thermal runaway of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a high-performance hydrogen sensor for early detection of thermal runaway of a lithium-ion battery, a preparation method and a state monitoring system. Background Art

[0002] New energy vehicles are in a stage of rapid development due to their advantages such as saving fuel energy, reducing exhaust emissions and low noise. Among them, lithium-ion batteries have become one of the most competitive energy storage technologies in the field of new energy vehicles due to their high energy density, long cycle life and green environmental protection.

[0003] Lithium-ion batteries are mainly composed of electrodes, polymer separators and liquid electrolytes, and are usually sealed with aluminum shells or plastic packaging. This will inevitably lead to poor heat dissipation during use, especially under extreme conditions such as overcharging and fast charging. The growth of lithium dendrites on the negative electrode causes perforation of the polymer film. After the separator loses its blocking effect, the direct contact between the positive and negative electrodes will cause an internal short circuit in the battery, generating more heat, further increasing the internal temperature, and triggering a series of disordered and intense chemical reactions, producing a large amount of flammable gases such as hydrogen, carbon monoxide, methane, etc.

[0004] Studies have shown that when a battery experiences thermal runaway, the hydrogen generated in the early stages of lithium battery overcharging comes from the chemical reaction between lithium dendrites and binders (PVDF or CMC+SBR), and has nothing to do with the electrolyte or other substances. This process occurs earlier than the decomposition of the SEI film. According to previous reports, hydrogen is generated 435s earlier than other gases. Therefore, the development of a hydrogen sensor with high sensitivity, short response time and good stability can effectively provide early warning for thermal runaway of lithium-ion batteries, thereby significantly reducing fire accidents caused by thermal runaway of batteries. Summary of the invention

[0005] The present invention provides a high-performance hydrogen sensor, preparation method and status monitoring system for early detection of thermal runaway of lithium-ion batteries, which can be used for rapid detection of hydrogen and have high sensitivity, short response / recovery time, good selectivity, repeatability and long-term stability, and can provide early warning for thermal runaway of lithium-ion batteries.

[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a high-performance hydrogen sensor for early detection of thermal runaway of lithium-ion batteries, comprising a sensing layer and a substrate, wherein the sensing layer is a sandwich structure consisting of a catalytic sensitization layer, a gas sensitive layer, and an electron supply layer, which are, from top to bottom, Ag@SnO2 catalytic sensitization layer, SnO2 gas sensitive layer, and g-C3N4 electron supply layer.

[0007] In some embodiments, the thicknesses of the catalytic sensitizing layer, the gas sensitive layer, and the electron supply layer are 100-300nm, 500-1000nm, and 500-1000nm, respectively; the particle size of SnO2 is 50-200nm; the particle size of Ag@SnO2 is 50-200nm; and the substrate can be an interdigitated electrode.

[0008] Preferably, the sensor has a detection limit of 30 ppb, a response / recovery time of 3 / 4 s, and a long-term stability of 50 days.

[0009] A second aspect of the present invention provides a method for preparing a high-performance hydrogen sensor for early detection of thermal runaway of a lithium-ion battery, comprising the following steps:

[0010] (1) Ag nanoparticles and SnO2 are mixed and stirred in deionized water, and Ag@SnO2 is obtained after washing and drying;

[0011] (2) mixing terpineol, ethyl cellulose and g-C3N4 nanosheets, grinding them, and then uniformly coating them on the surface of a substrate, and drying them to obtain a substrate coated with an electron supply layer;

[0012] (3) mixing pinene alcohol, ethyl cellulose and SnO2 and grinding them, and then uniformly coating them on the substrate obtained in step (2), and drying them to obtain a substrate coated with a gas sensitive layer-electron supply layer;

[0013] (4) mixing pinene alcohol, ethyl cellulose and Ag@SnO2 and grinding them, and then uniformly coating them on the substrate obtained in step (3), and drying them to obtain a substrate coated with a catalytic sensitization layer, a gas sensitive layer and an electron supply layer;

[0014] (5) calcining the substrate to obtain the high-performance hydrogen sensor.

[0015] Furthermore, in step (1), the molar ratio of Ag nanoparticles to SnO2 is (1-2):(100-200), and the stirring time is 12-24h.

[0016] Furthermore, in the step (2), the mixing ratio of pinene alcohol, ethyl cellulose and g-C3N4 nanosheets is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g; in the step (3), the mixing ratio of pinene alcohol, ethyl cellulose and SnO2 is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g; and in the step (4), the mixing ratio of pinene alcohol, ethyl cellulose and Ag@SnO2 is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g.

[0017] Furthermore, in step (5), the calcination temperature is 600-650°C and the calcination time is 1-1.5h. During the calcination process, the material undergoes recrystallization, making the material structure more aggregated. At the same time, during this process, the contact between the catalytic sensitization layer, the gas sensitive layer and the electron supply layer is more stable, which is conducive to the transmission of electrons at the interface, thereby further improving the gas sensing performance of the sensor device.

[0018] In some embodiments, the Ag nanoparticles are prepared by reacting a silver nitrate solution with a sodium citrate solution under heating; preferably, the concentration of the silver nitrate solution is 1-1.5 mol / L, the concentration of the sodium citrate solution is 0.1-0.15 mol / L, the heating temperature is 90-100°C, and the reaction time is 0.3-0.5h.

[0019] In some embodiments, the g-C3N4 nanosheets are prepared by high-temperature calcination of urea; preferably, the calcination temperature is 550-600°C, the calcination time is 3-4h, and the heating rate is 10-15°C / min.

[0020] A third aspect of the present invention provides a state monitoring system, comprising a test module, a voltage-boosting circuit control module, a signal conversion module, a control module and a display module;

[0021] The test module includes the above-mentioned high-performance hydrogen sensor, which is used to obtain a hydrogen concentration signal in the environment, wherein the hydrogen concentration signal is an analog electrical signal;

[0022] The voltage-boosting circuit control module is used to receive the analog electrical signal output by the signal conversion module and adjust the circuit voltage to control the temperature rise and fall of the test module;

[0023] The signal conversion module is used to convert the digital electrical signal output by the control module into an analog electrical signal;

[0024] The control module is connected to the step-up / step-down circuit control module, the signal conversion module, and the display module, and is used to control the conversion of circuit voltage and electrical signals and the output of detection results;

[0025] The display module is used to display the detection result of hydrogen concentration.

[0026] The control module also has a signal conversion unit, which is connected to the display module; the signal conversion unit is also connected to the test module, and is used to convert the analog electrical signal output by the test module into a digital electrical signal.

[0027] A fourth aspect of the present invention provides an application of the above-mentioned sensor or the sensor prepared according to the above-mentioned preparation method, wherein the application includes battery thermal runaway warning.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The Ag nanoparticles in the hydrogen sensor of the present invention are in an amorphous state at 300°C, have abundant crystal defects and high reactivity, and provide a large number of active sites for gas adsorption and redox reactions. In this state, due to the low reaction activation energy, it is very easy to undergo adsorption reaction with the target gas. Due to the catalytic effect and overflow effect of the Ag nanoparticles, the sensor has a short response / recovery time, a low detection limit, and good stability and repeatability.

[0030] (2) Since the electron supply layer supplies a large number of active electrons to the gas sensitive layer, coupled with the electron sensitization effect of the catalytic sensitizing layer, the reaction activity of the gas sensitive layer is greatly improved, providing more reaction active sites for the redox reaction of the target gas, thereby further improving the gas sensitive performance of the sensor. Compared with other types of sensors, the sensor of the present invention has the highest response value and exhibits excellent selectivity, which can effectively warn the occurrence of battery thermal runaway. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the sensor preparation process of the present invention;

[0032] Figure 2 XRD patterns of Ag@SnO2, SnO2 and g-C3N4;

[0033] Figure 3 (a)-3(d) are SEM images of SnO2, Ag@SnO2, g-C3N4 and the sensor of the present invention, respectively; Figure 3 (e) -3(f) are TEM and HRTEM images of Ag@SnO2, respectively;

[0034] Figure 4 (a) is the response curve of the sensor detecting 50 ppm H2 at different temperatures; Figure 4 (b) Response / recovery curve of the sensor detecting H2 at the optimal working temperature; Figure 4 (c) is the linear relationship of the sensor detecting different concentrations of H2 at the optimal working temperature; Figure 4 (d) Response / recovery time of the sensor detecting 50 ppm H2 at the optimal operating temperature; Figure 4 (e) Short-term repeatability test of the sensor detecting 50 ppm H2 at the optimal operating temperature; Figure 4 (f) Long-term stability test of the sensor detecting 50 ppm H2 at the optimal operating temperature;

[0035] Figure 5(a) is the response recovery curve of the sensor of the present invention; Figure 5 (b) is the linear curve of the sensor detecting different concentrations of H2 at the optimal working temperature; Figure 5 (c) is the response diagram of the sensor detecting 50ppm H2, CO2, CO and CH4;

[0036] Figure 6 HRTEM images (af, a1-f1) and selected area electron diffraction (SAED) images (a2-f2) of Ag nanoparticles at different temperatures;

[0037] Figure 7 (a)-7(d) are the DOS results of H2, CO, CO2 and CH4 adsorption models respectively;

[0038] Figure 8 is the IV characteristic curve of the sensor sensing layer material;

[0039] Fig. 9 (a)-9(b) are schematic diagrams of the sensing mechanism of the sensor of the present invention in atmospheric environment and hydrogen environment respectively; Fig. 9 (c) Schematic diagram of the energy band structure of the sensor in atmospheric environment and hydrogen environment;

[0040] Fig.10 (a) is the front side of the sensor substrate of the present invention; Fig.10 (b) is the back side of the sensor substrate of the present invention; Fig.10 (c) is the internal structure diagram of the sensor before packaging; Fig.10 (d) is the sensor after packaging; Fig.10 (e) is a schematic diagram of the circuit module structure of the condition monitoring system; Fig.10 (f) The test results of the condition monitoring system placed in the atmospheric environment; Fig.10 (g) shows the test results of the condition monitoring system placed in a 5 ppm H2 environment;

[0041] Fig.11 It is a real-time detection system for battery thermal runaway status. DETAILED DESCRIPTION

[0042] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0043] In the following examples, the raw materials were purchased from Sinopharm Chemical Reagent Co., Ltd., China, and used in the experiments without further purification. Figure 1 This is a schematic diagram of the sensor preparation process of the present invention.

[0044] A method for preparing a high-performance hydrogen sensor for early detection of thermal runaway of a lithium-ion battery comprises the following steps:

[0045] (1) 1 mol / L AgNO3 solution and 0.1 mol / L sodium citrate solution were mixed in a volume ratio of 1:10, and the solution was heated at 100°C to keep boiling for 0.5 hours to finally obtain a yellow-green Ag nanoparticle solution;

[0046] (2) Take 0.2 mL of yellow-green Ag nanoparticle solution and 0.15 g SnO2 and add them to deionized water (wherein the molar ratio of Ag nanoparticles to SnO2 is 1:100) and stir continuously for 12 h. Then wash with deionized water and ethanol three times respectively. Finally, place the washed product in a vacuum drying oven and dry it at 50 °C for 12 h to obtain Ag@SnO2 gray powder.

[0047] (3) Urea was placed in an alumina crucible with a lid, and then the crucible was placed in a muffle furnace, and the temperature was raised to 550°C at a heating rate of 15°C / min, and kept warm for 3 hours. Then, the mixture was washed with deionized water and ethanol three times respectively, and vacuum dried at 70°C for 12 hours to obtain a light yellow g-C3N4 nanosheet powder;

[0048] (4) Grind terpineol, ethyl cellulose and g-C3N4 nanosheets in a mortar at a ratio of 3.5 mL: 0.54 g: 0.2 g until a suspension is obtained, and then spin-coat the suspension on the surface of a substrate using a pipette to form a thin film, and dry it at 60 ° C for 12 h to finally obtain a substrate coated with an electron supply layer;

[0049] (5) Grind and mix terpineol, ethyl cellulose and SnO2 in a mortar in a ratio of 3.5 mL: 0.5 g: 0.2 g, and then spin-coat the mixture on the surface of the substrate coated with the electron supply layer. After drying, obtain a substrate coated with a gas sensitive layer-electron supply layer;

[0050] (6) Grind and mix terpineol, ethyl cellulose and Ag@SnO2 in a mortar in a ratio of 3.5 mL: 0.54 g: 0.15 g, and then spin-coat the mixture on the surface of the substrate coated with the gas sensitive layer-electron supply layer. After drying, a substrate coated with a catalytic sensitization layer-gas sensitive layer-electron supply layer is obtained.

[0051] (7) The substrate is calcined at 600° C. for 1 hour to obtain a high-performance hydrogen sensor for early detection of thermal runaway of a lithium-ion battery.

[0052] Figure 2The XRD diagrams of Ag@SnO2, SnO2 and g-C3N4 of the present invention are as shown in the figure. The materials have good crystallinity and high purity. The diffraction peaks of a single SnO2 sample at 26.5°, 33.8°, 37.9°, 38.9°, 42.6°, 51.7°, 54.7°, 57.8°, 61.8°, 64.7°, 65.9°, 71.3° and 78.7° are indexed as body-centered cubic structure SnO2 (110), (101), (200), (111), (210), (211), (220), (002), (310), (112), (301), (202) and (321) crystal planes (JCPDS72-1147), respectively. The diffraction peaks of Ag@SnO2 and SnO2 are almost the same. Due to the low content of Ag nanoparticles, the diffraction peak of the (200) crystal plane of Ag nanoparticles at 44.3° can only be seen under local magnification.

[0053] Figure 3 The microstructures of SnO2, Ag@SnO2, g-C3N4 and the sensor of the present invention are shown. Figure 3 (a) is pure SnO2 nanoparticles with a particle size distribution between 50 and 200 nm; Figure 3 (b) Ag@SnO2 composite material, with a particle size distribution between 50-200nm. Compared with pure SnO2, the number of Ag@SnO2 particles with a particle size of about 50nm increases significantly due to the introduction of Ag nanoparticles; Figure 3 (c) is pure g-C3N4 nanosheets. g-C3N4 is a two-dimensional graphene-like layered structure, which can provide a large contact area for SnO2 nanoparticles and is more conducive to electron transfer between the two.

[0054] The high-performance hydrogen sensor of the present invention comprises a sensing layer and a substrate. Figure 3 (d) is a SEM image of the sensor of the present invention. As shown in the figure, the sensing layer of the sensor of the present invention is a sandwich structure consisting of a catalytic sensitization layer, a gas sensitive layer, and an electron supply layer, which are Ag@SnO2 catalytic sensitization layer, SnO2 gas sensitive layer, and g-C3N4 electron supply layer from top to bottom. The thickness of the catalytic sensitization layer, the gas sensitive layer, and the electron supply layer are 300nm, 1000nm, and 1000nm, respectively. Figure 3 (e)-3(f) The presence of Ag and SnO2 can be clearly distinguished by lattice fringes and lattice spacing.

[0055] Performance Testing

[0056] Figure 4The gas-sensing performance of the high-performance hydrogen sensor (or CSE sensor, the sensing layer, i.e., the sensitive material is Ag@SnO2@g-C3N4), SE (the sensing layer, i.e., the sensitive material is the gas sensitive layer-electron supply layer, i.e., SnO2@g-C3N4), CS (the sensing layer, i.e., the sensitive material is the catalytic sensitization layer-gas sensitive layer) and pure SnO2 sensor (the sensing layer, i.e., the sensitive material is SnO2) of the present invention in detecting H2 is demonstrated. Figure 4 (a) (from top to bottom: CSE, CS, SE, SnO2) shows the changes in the response values ​​of different sensors for detecting 50ppm H2 at different temperatures. From the test results, it can be found that the addition of Ag nanoparticles effectively reduces the operating temperature of the sensor. The optimal operating temperatures of CS and CSE sensors are both 300℃, which is 50℃ lower than that of the other two materials. The gas sensing performance of different sensors at the optimal operating temperature is tested, such as Figure 4As shown in (b) (from top to bottom, CSE, CS, SE, SnO2), at the optimal operating temperature, since g-C3N4 acts as an electron supply layer, it provides a large number of active electrons for the SnO2 gas sensitive layer, greatly increasing the adsorption sites of active oxygen species and improving the gas sensing performance. Therefore, the response value of the CSE sensor is much higher than that of the CS sensor; at the optimal operating temperature, the response value of the CSE sensor is much higher than that of the SE sensor. This is because the work functions of Ag nanoparticles and SnO2 are different, and charge transfer occurs at the interface between the two, forming a potential barrier, which increases the separation rate of electron-hole pairs in the SnO2 gas sensitive layer, thereby improving the utilization rate of active electrons, increasing the adsorption sites of active oxygen species, and thus improving the gas sensing performance. In addition, the inherent catalytic effect and overflow effect of Ag nanoparticles as noble metals also make the performance of CSE sensors better than that of SE sensors. At the same time, compared with the pure SnO2 sensor, the baseline resistance of the binary composite material sensor is increased, and the baseline resistance of the ternary material is the highest. This is because in SnO2@g-C3N4, due to the different Fermi levels of SnO2 and g-C3N4, charge transfer occurs at the interface between the two, causing the energy bands of the two to bend to form a potential barrier, which hinders the transmission of electrons and thus increases the baseline resistance of the material; in Ag@SnO2, due to the different work functions of Ag and SnO2, charge transfer occurs at the interface between the two to form a potential barrier, which hinders the transmission of electrons and thus increases the baseline resistance of the material; in Ag@SnO2@g-C3N4, due to the simultaneous existence of the above two barriers, the ternary composite material has the highest baseline resistance. In addition, compared with pure SnO2 and SE sensors, the resistance change rate of CS and CSE sensors in high concentration H2 environment (20-60ppm) decreases faster with the increase of hydrogen concentration. This is due to the catalytic effect and spillover effect of Ag nanoparticles, which decompose H2 molecules into hydrogen atoms. Compared with H2 molecules, hydrogen atoms occupy more active adsorption sites, resulting in the Ag-modified composite material reaching the saturation value of hydrogen adsorption earlier than the other two materials. The linear relationship between the response value and concentration of different sensors detecting different concentrations of H2 was tested, and the test results are as follows: Figure 4 As shown in (c) (from top to bottom: CSE, SE, CS, SnO2), it can be seen from the figure that with the change of hydrogen concentration, the response values ​​of the four sensors show a good linear relationship with the concentration. Through the formula LOD = 3σ (baseline standard deviation) / S (fitting curve slope), it can be obtained that the detection limits of the four sensors SnO2, SE, CS and CSE are 900ppb, 100ppb, 150ppb, and 30ppb respectively. The response / recovery time of the four sensors to detect 50ppm H2 was tested, and the test results are shown in Figure 4As shown in (d), the response / recovery speed of the SE sensor (87 / 117s) is the slowest. This is because the electron supply layer provides a large number of active electrons, thereby increasing the number of active oxygen species adsorption sites. Therefore, compared with the pure SnO2 sensor (response / recovery speed of 26 / 14s), the response value is improved, and the redox reaction time of the surface adsorbed gas is also increased. Both CS and CSE sensors have faster response / recovery speeds (9 / 5s, 3 / 4s). This is because the catalytic effect and spillover effect of Ag nanoparticles decompose H2 molecules into H, which has higher activity and lower reaction activation energy than H2 molecules and can quickly undergo redox reactions with oxygen species. Figure 4 (e) shows the short-term repeatability of the CSE sensor in detecting H2. The test results show that the CSE sensor has good short-term repeatability in detecting H2. Long-term stability is also one of the important indicators for evaluating gas sensors. The long-term stability of the CSE sensor is as high as 50 days. Figure 4 (f) as shown.

[0057] In addition, the performance of CSE sensor in detecting ppb level H2 was evaluated. The test results are as follows: Figure 5 As shown in the test results, it can be found that within the concentration range of 30-500ppb, as the concentration of the target gas continues to rise, the detection response curve of the CSE sensor also changes significantly ( Figure 5 (a)), by Figure 5 (b) It can be seen that within the detection concentration range, the gas concentration and the response value have a good linear correspondence. Therefore, the test results show that the CSE sensor has a good ability to detect ppb-level H2 at the optimal operating temperature (300°C). The rapid detection and recovery of H2 can effectively prevent the occurrence of thermal runaway accidents in lithium-ion batteries. Since four main gases, H2, CO2, CO and CH4, are produced when thermal runaway of lithium-ion batteries occurs, in order to test the selectivity of the sensor to H2, the four sensors are tested on the above four gases respectively. The results are shown in Figure 2. Figure 5 (c) It can be seen that since the gas sensitive layers are all based on SnO2, the four sensors have good selectivity for H2. However, with the addition of the catalytic sensitization layer and the electron supply layer, the gas sensing performance of the CSE sensor in detecting H2 is even better.

[0058] In order to further explore the reasons why the optimal operating temperature of CS and CSE sensors is low, the crystallization properties of Ag nanoparticles were further studied by variable temperature HRTEM. The test results are as follows: Figure 6 As shown. At 100℃-150℃ ( Figure 6 a-6b), at the same position of the material (red circle), the lattice fringes are clear and closely spaced ( Figure 6a1-6b1), the corresponding SAED diffraction rings ( Figure 6 a2-6b2) is very clear, which proves that the material is well crystalline at this time. When the temperature is further increased to 200-250℃ ( Figure 6 c-6d), the lattice fringe spacing at the same position of the material is significantly increased ( Figure 6 c1-6d1), which may be attributed to the fact that as the temperature increases, the atomic energy gradually increases, the lattice vibration becomes more obvious, resulting in an increase in the lattice fringe spacing, and its SAED diffraction ring ( Figure 6 c2-6d2) also gradually fades. When the temperature rises to 300℃ ( Figure 6 e), no obvious lattice can be observed at the same position of the material ( Figure 6 e1, and at this temperature the diffraction rings ( Figure 6 e2) is no longer clear, which indicates that Ag exists in the composite material in an amorphous state at 300℃. When the temperature rises to 350℃ ( Figure 6 f), at the same position of the material, the lattice fringes gradually become clearer ( Figure 6 f1), and the SAED diffraction rings ( Figure 6 f2) is also clearer than at 300℃, which indicates that the Ag nanoparticles recrystallized at 350℃. Ag nanoparticles are amorphous at 300℃. Compared with crystalline Ag nanoparticles, amorphous Ag nanoparticles have more defects and higher reactivity. At this temperature, their excellent properties such as catalytic properties and spillover effect are brought to the extreme. Therefore, the CSE sensor exhibits the best gas sensing performance at 300℃.

[0059] Table 1 Energy statistics of adsorption model for different gases

[0060]

[0061] In order to explore the reasons why CSE sensors have good selectivity for H2, the charge density change and adsorption energy of the gas sensitive layer before and after gas adsorption were theoretically studied by first principles. The adsorption model was established by MaterialStudio (MS) and the Dmol 3 The density functional theory (DFT) in the module was used to study the adsorption performance of the model. All calculations were performed using Grimme empirical diffusion correction DFT-D, and the generalized gradient approximation (GGA) and the Poderberk-Enzerhof (PBE) function were used to calculate the electron exchange energy. The convergence value of the energy was set to 2.0×10 −5Ha, the maximum force and maximum distance are set to 0.04Ha / Å and 0.005Å respectively, and the maximum number of iterations is 900. The (110) crystal plane of SnO2 is used as the adsorption surface for this modeling. The calculation results are shown in Table 1 and can be obtained by the following formula: E ad = E gas / system – E gas – E system , calculate the size of the sensor's adsorption energy for different gases, where E gas / system is the energy of the adsorption model after the gas is adsorbed, E gas With E system They are the energies of a single gas and a single adsorption model. Through calculation, it can be seen that the adsorption energy of the sensor for H2 is much higher than that of the other three gases. Therefore, compared with the other three gases, the CSE sensor shows the best gas-sensitive performance for H2.

[0062] In order to further explore the reason why the CSE sensor has the highest adsorption energy for H2, the density of states (DOS) of the four gas adsorption models were calculated respectively. The calculation results are shown in Figure 7 As shown in the DOS diagram of the H2 adsorption model, it can be seen that the two peaks of the H atom 1s orbit at -10~-8eV and the peak at 2~6eV are highly coincident with the peaks of the 5s and 2p orbits corresponding to the Sn and O atoms in the gas sensitive layer, respectively, indicating that the electron orbits of the H atom are highly hybridized with the electron orbits of the Sn and O atoms in the gas sensitive layer, so the gas sensitive layer has a higher adsorption energy for H2. Since the electron orbits of the other three gases are weakly hybridized with the atomic orbits of the gas sensitive layer, the adsorption energy is lower.

[0063] Gas-sensing mechanism

[0064] Due to the charge transfer between Ag nanoparticles and C3N4 nanosheets and SnO2, the gas sensing performance of the CSE sensor was improved through the electronic sensitization effect, showing excellent gas sensing properties for H2. To prove that charge transfer occurred between different materials, the current-voltage (I-V) characteristics of the four sensor sensing layer materials were studied using Keithley-2400 (a bias voltage of −5V to +5V was used during the test). The results are shown in the figure. Figure 8 The SnO2 sensor has a good linear relationship between current and voltage, indicating that a single pure material has good ohmic characteristics. Since the IV characteristics of the non-single material sensor show nonlinear changes and rectification, it indicates that there is charge transfer between the contact surfaces of the non-single material and a heterogeneous structure is formed.

[0065] Fig. 9 The sensing mechanism of the CSE sensor is demonstrated. Fig. 9As shown in (a), when the operating temperature is 300°C, the CSE sensor is placed in the atmosphere, and the O2 molecules adsorbed on the surface of the sensor sensing layer material will deprive the electrons in the conduction band of the material to form active oxygen species (O - ), the resistance obtained at this time is the baseline resistance Ra. When H2 is introduced, the H2 molecules are catalyzed by the Ag nanoparticles to decompose into H ads atoms and overflow to the surface of SnO2 (such as Fig. 9 (b)), atoms have higher reactivity and lower reaction activation energy than H2 molecules, so this overflow effect can make O - With H ads The redox reaction occurs rapidly, and the above reaction process is shown in the following formula.

[0066] O 2(ads) +2e - →2O - (ads)

[0067] H 2(gas) →H (ads)

[0068] O - (ads) + H (ads) →OH - (ads)

[0069] OH - (ads) + H (ads) →H2O (gas) +e -

[0070] The above redox reaction makes O - The electrons are released back to the conduction band of the material. At this time, the baseline resistance Ra will decrease until it stabilizes to the response resistance Rg. This process is a typical gas-sensitive response process of n-type semiconductors to test reducing gases. On the other hand, since the redox reaction process is carried out by H with higher reaction activity, ads Atoms replace H2 molecules to participate in the reaction, which will greatly increase the reaction rate and thus greatly shorten the response / recovery time of gas detection.

[0071] In addition to catalytic sensitization and spillover effect, which can effectively improve the gas-sensing performance of gas sensors, electronic sensitization effect is also an important strategy to improve the gas-sensing performance of sensors. Fig. 9 c is a schematic diagram of the energy band structure of the CSE sensor in the atmosphere and hydrogen environment, showing the electron transfer process between CSE sensor materials and the electron sensitization mechanism. Fig. 9As shown in Figure c, when the sensor materials are in contact with each other, since the work functions of Ag nanoparticles and g-C3N4 are both smaller than SnO2 in the gas sensitive layer, electrons flow from Ag nanoparticles and g-C3N4 nanosheets to SnO2 until the Fermi levels of the three reach equilibrium. At the same time, with the transfer of electrons, a built-in electric field will be generated at the interface of the material. The direction of the electric field is just opposite to the transmission direction of the electrons and hinders the movement of the electrons. This process is the formation process of the potential barrier (qV). qV is one of the important factors affecting the baseline resistance Ra of the sensing material. The relationship between the two is as follows: Ra∝exp(-qV / 2kT), where Ra represents the resistance of the sensor, qV represents the barrier height, k represents the Boltzmann constant, and T represents the absolute temperature. From the above formula, we can see that the baseline resistance increases with the increase of potential barriers, which fully explains why the baseline resistance of CSE sensors is the highest. On the other hand, the existence of potential barriers can effectively increase the separation rate of electron-hole pairs in the sensing material, which will lead to an increase in the number of active electrons in the conduction band of the sensor material, thereby increasing the number of active adsorption sites on the surface of the material. All of the above can effectively improve the gas sensing performance of the gas sensor. When the CSE sensor is placed in a H2 environment from an atmospheric environment, O - Will be with H ads A redox reaction occurs during which O - The release of electrons back into the conduction band of the sensor material leads to the thickening of the electron accumulation layer at the interface of the composite material, the lowering of the potential barrier, and finally the decrease of the resistance of the material until it stabilizes to Rg.

[0072] The present invention also provides a state monitoring system, which comprises a test module, a voltage-boosting circuit control module, a signal conversion module, a control module and a display module.

[0073] like Fig.10 (a) shows the front side of the sensor substrate of the present invention, which has a size of only 2 mm, and the two metal wire electrodes led out are test electrodes; Fig.10 (b) shows the back side of the sensor substrate of the present invention, wherein the middle black part is the heating material, and the two metal wire electrodes led out from the back side are heating electrodes with adjustable voltage. By adjusting the voltage at both ends, higher and different operating temperatures can be provided for the sensor. Fig.10 (c) is the internal structure diagram of the sensor before packaging. In the figure, the four circular pillars support the sensor through soldering, which can provide sufficient heat dissipation space for the sensor working at high temperature; Fig.10 (d) shows the sensor probe after packaging, in which the two electrodes at the end with the protrusion are heating electrodes, and the two electrodes at the end without the protrusion are testing electrodes. Fig.10(e) shows a schematic diagram of the circuit module structure of the state monitoring system of the present invention. As shown in the figure, the state monitoring system includes a test module, a boost-buck circuit control module, a signal conversion module, a control module and a display module; the core component of the test module is a high-performance hydrogen sensor, which is used to obtain the hydrogen concentration signal in the environment, and the hydrogen concentration signal is an analog electrical signal; the signal conversion module is used to convert the digital electrical signal output by the control module into an analog electrical signal, and the digital-to-analog conversion chip model used in this module is MS5614; the boost-buck circuit control module is used to receive the analog electrical signal output by the signal conversion module and adjust the circuit voltage to control the temperature rise and fall of the test module, that is, through two FP5139 boost-buck converter control chips The minimum duty cycle of the test boost-buck circuit and the heating boost-buck circuit is controlled to control the output voltage of the two circuits; the control module is connected with the boost-buck circuit control module, the signal conversion module and the display module, and is used to control the conversion of the circuit voltage and the electrical signal and the output of the detection result. It is mainly composed of electronic devices such as an STM32 microprogram controller, and the entire detection system is controlled in a code manner to realize the sensing detection function of the system. The control module also has a signal conversion unit, which is connected with the display module; the signal conversion unit is also connected with the test module, and the signal conversion unit is used to convert the analog electrical signal output by the test module into a digital electrical signal; the last part is the display module, which is used to display the detection result of the hydrogen concentration. Specifically, the control module sends a digital electrical signal to the signal conversion module, the signal conversion module converts the digital electrical signal output by the control module into an analog electrical signal, and outputs the analog electrical signal to the step-up and step-down circuit control module, wherein the FP5139 chip controls the test voltage and heating voltage of the sensor by controlling the step-up and step-down circuit. Subsequently, the sensor detects the hydrogen concentration in the environment at a certain working temperature and outputs an analog electrical signal, and inputs the analog electrical signal into the signal conversion unit of the control module for conversion into a digital electrical signal. Finally, the detection result of the hydrogen concentration is presented through the display unit.

[0074] Fig.10 (f) is the test result of the test system placed in the atmospheric environment, Fig.10 (g) shows the test results of the detection system placed in a 5ppm H2 environment. In addition, the state monitoring system is combined with the host computer to build a complete battery thermal runaway state real-time detection system. The results are shown in Fig.11 shown.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. High-performance hydrogen sensor for early detection of thermal runaway of lithium-ion batteries, characterized by: The sensor includes a sensing layer and a substrate. The sensing layer is a sandwich structure consisting of a catalytic sensitization layer, a gas sensitive layer, and an electron supply layer, which are Ag@SnO2 catalytic sensitization layer, SnO2 gas sensitive layer, and g-C3N4 electron supply layer from top to bottom.

2. The high performance hydrogen sensor according to claim 1, characterized in that: The thicknesses of the catalytic sensitization layer, the gas sensitive layer and the electron supply layer are 100-300nm, 500-1000nm and 500-1000nm respectively; the particle size of SnO2 is 50-200nm; and the particle size of Ag@SnO2 is 50-200nm.

3. The high performance hydrogen sensor according to claim 1, characterized in that: The sensor has a detection limit of 30 ppb, a response time of 3 s, a recovery time of 4 s, and a long-term stability of 50 days.

4. The method for preparing a high-performance hydrogen sensor according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) Ag nanoparticles and SnO2 are mixed and stirred in deionized water, and Ag@SnO2 is obtained after washing and drying; (2) mixing terpineol, ethyl cellulose and g-C3N4 nanosheets, grinding them, and then uniformly coating them on the surface of a substrate, and drying them to obtain a substrate coated with an electron supply layer; (3) mixing pinene alcohol, ethyl cellulose and SnO2 and grinding them, and then uniformly coating them on the substrate obtained in step (2), and drying them to obtain a substrate coated with a gas sensitive layer-electron supply layer; (4) mixing pinene alcohol, ethyl cellulose and Ag@SnO2 and grinding them, and then uniformly coating them on the substrate obtained in step (3), and drying them to obtain a substrate coated with a catalytic sensitization layer, a gas sensitive layer and an electron supply layer; (5) calcining the substrate to obtain the high-performance hydrogen sensor.

5. The preparation method according to claim 4, characterized in that: In the step (1), the molar ratio of Ag nanoparticles to SnO2 is (1-2):(100-200), and the stirring time is 12-24h.

6. The preparation method according to claim 4, characterized in that: In the step (2), the mixing ratio of pinene alcohol, ethyl cellulose and g-C3N4 nanosheets is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g; in the step (3), the mixing ratio of pinene alcohol, ethyl cellulose and SnO2 is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g; in the step (4), the mixing ratio of pinene alcohol, ethyl cellulose and Ag@SnO2 is (3.5-4) mL: (0.5-0.54) g: (0.1-0.2) g.

7. The preparation method according to claim 4, characterized in that: In the step (5), the calcination temperature is 600-650° C. and the calcination time is 1-1.5 h.

8. Use of the sensor according to any one of claims 1 to 3 or the sensor prepared by the preparation method according to any one of claims 4 to 7, characterized in that: The applications include battery thermal runaway early warning.

9. A condition monitoring system, characterized in that: The state monitoring system includes a test module, a voltage-boosting circuit control module, a signal conversion module, a control module and a display module; The test module comprises a high-performance hydrogen sensor as claimed in any one of claims 1 to 3, which is used to obtain a hydrogen concentration signal in the environment, wherein the hydrogen concentration signal is an analog electrical signal; The voltage-boosting circuit control module is used to receive the analog electrical signal output by the signal conversion module and adjust the circuit voltage to control the temperature rise and fall of the test module; The signal conversion module is used to convert the digital electrical signal output by the control module into an analog electrical signal; The control module is connected to the step-up / step-down circuit control module, the signal conversion module, and the display module, and is used to control the conversion of circuit voltage and electrical signals and the output of detection results; The display module is used to display the detection result of hydrogen concentration.

10. The condition monitoring system according to claim 9, characterized in that: The control module also has a signal conversion unit, which is connected to the display module; the signal conversion unit is also connected to the test module, and is used to convert the analog electrical signal output by the test module into a digital electrical signal.

Citation Information

Patent Citations

  • Carbon nitride material, preparation method of carbon nitride material, gas-sensitive sensor and preparation method of gas-sensitive sensor

    CN104671244A

  • Hydrogen sensor based on MXene-SnO2 composite sensitive material as well as preparation method and application of hydrogen sensor

    CN117110382A